Antonyms of English and Kazakh Languages and Their Structural Features - Tukeshova, N. M.; Tarasova, F. K.; Yerbulatova, I. K. (APPLIED LINGUISTICS RESEARCH JOURNAL. - 2020, 2020)
Despite the fact that English and Kazakh languages are rich in antonyms, which are universal phenomenon, in particular, the comparative study of antonyms in English and Kazakh languages is almost incomplete. In order to supplement it, the article provides an overview of the concept of antonyms in English and Kazakh languages, and reveals how often antonyms have been studied by other researchers. Conducted analysis of antonyms in English and Kazakh languages reveals the structural features of each language, their similarities and differences. Also, examples of antonyms as part the phraseological units with antonymous components were given, which were taken and analyzed from lexicographic dictionaries of the two studied languages, and based on the analysis of the dictionaries, it was determined how often different root and single -root antonyms occur. The practical significance of this work may affect its use in the teaching of the two languages under study, in comparative linguistics. Несмотря на то, что английский и казахский языки богаты антонимами, которые являются универсальным явлением, в частности, сравнительное изучение антонимов в английском и казахском языках практически не завершено. Чтобы дополнить его, в статье дается обзор концепции антонимов в английском и казахском языках и раскрывается, насколько часто антонимы изучались другими исследователями. Проведенный анализ антонимов в английском и казахском языках позволяет выявить структурные особенности каждого языка, их сходства и различия. Также были приведены примеры антонимов в составе фразеологизмов с антонимными компонентами, которые были взяты и проанализированы из лексикографических словарей двух изучаемых языков, и на основе анализа словарей было определено, насколько часто различаются коренные и однокорневые встречаются антонимы. Практическое значение этой работы может повлиять на ее использование при преподавании двух изучаемых языков в сравнительной лингвистике.
Keywords: томсон; кларивате аналитикс; языкознание; казахский язык; английский язык; зарубежное издание; дальнее зарубежье; импакт-фактор 2020; научный журнал; периодическое издание; электронный эурнал; зарубежные авторы